Stereoselective Synthesis of Highly Substituted α‐Silylamines from Silylmethyl Azides under Ru Catalysis. Issue 34 (22nd October 2014) - Jeong, Wook; Kim, Jungjoon; Park, Jaiwook; Rhee, Young Ho
Abstract: A synthetic strategy towards highly substituted α‐silyl homoallylic amines was discovered. The key event is the unique synthesis of N ‐unsubstituted α‐silylimines from azide precursors under mild conditions. Of particular note is the unprecedented access to α‐silylamines possessing multiple stereocenters and functional groups with high diastereo‐ and enantioselectivity. The synthetic utility of the method was demonstrated by the use of the silyl moiety as the key element that enables late‐stage modification for the iminium ion mediated oxidative cyclization. Abstract : A diastereo‐ and enantioselective synthesis of highly functionalized α‐silyl homoallylic amines is reported. This new reaction is promoted by unique access to N ‐unsubstituted α‐silylimines from azide precursors, which is conducted under mild Ru catalysis and photolytic conditions; pin = pinacolyl.